The Role of Agricultural Extension Counselors in Supporting the Robusta Coffee Crop Intensification Program to Increase Farmers' Income - Ni Luh Made Indah Murdyani Dewi; Gede Mekse Korri Arisena; Ni Made Agnis Ranadewi; Ni Ketut Selamat Kariyani; Ni Wayan Atik Sarmila Dewi (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2025)
The decline in robusta coffee production in 2022 has become a significant problem for farmers in Belatungan Village, Pupuan District, Tabanan Regency. The main causes of this decline in production are pest attacks, lack of garden maintenance, and limited production facilities. This study aims to analyze the role of agricultural extension workers in supporting the robusta coffee crop intensification program, identify the benefits of intensification on productivity, and measure its impact on farmers' income. The study was conducted in Belatungan Village using qualitative and quantitative descriptive methods. Data were collected through interviews and observations of two farmer groups participating in the intensification program, consisting of 80 respondents, including 50 farmers from Subak Abian Bwana Manik Sari and 30 farmers from the Gastam Farmer Group.  To answer the research questions, a Likert scale approach was used to determine the benefits of this intensification program, and farm income analysis was used. The results showed that the intensification of robusta coffee significantly increased crop productivity and farmer income. On average, farmer income tripled after the intensification program. However, this study was limited to a small area and did not evaluate the sustainability of the program. Recommendations for further research include expanding the coverage area and examining the sustainability factors and environmental impacts of robusta coffee intensification.